Investigation into effective mechanical properties of porous material produced by the additive manufacturing method (Fracture and Structural Integrity, 2023)
Porous materials are defined as materials that contain holes, voids, or spaces in their structures, which can be interconnected or isolated. In the most complex forms of these materials, the holes can have irregular shapes with a random distribution in size, location, and direction, making studying their properties a challenging problem. Additive manufacturing techniques offer opportunities to create complex structures, and in this paper, we investigate the effective mechanical properties of porous material produced by the Fused Displacement Modeling (FDM) technique. We also propose an algorithm for generating a porous body containing irregularly shaped holes with arbitrary distributions in size and location while maintaining specific porosity. Due to the orthotropic properties of bodies created by the FDM technique, Reinforced Isotropic Solid Modeling (RISM) is combined with existing theories that calculate the effective properties of isotropic materials. For the experiments, some modified standard specimen with a porosity of 0.05 to 0.40 has been fabricated, and the elastic modulus and ultimate stress have been calculated using the tensile test. Finally, the results are compared with experimental data.
Keywords: Porous material; Additive manufacturing; Reinforced isotropic material; Effective properties